Global trends in burden of type 2 diabetes attributable to physical inactivity across 204 countries and territories, 1990-2019 - Yang, Xinyue; Sun, Jiayi; Zhang, Wenjuan (Frontiers in Endocrinology, 2024)
Background: To promote a comprehensive understanding of global trends and burden of type 2 diabetes attributable to physical inactivity.We utilized data regarding mortality, disability-adjusted life years (DALYs), as well as age-standardized mortality rates (ASMR) and DALYs rates (ASDR) derived from the global burden of disease study 2019 to evaluate the impact of physical inactivity on the prevalence of type 2 diabetes in 204 countries and territories over the period from 1990 to 2019. This method facilitated the analysis of the diabetes burden across different ages, genders, and regions. To determine the long-term progression of type 2 diabetes prevalence, we computed the estimated annual percentage change (EAPC) in burden rates.Results: Globally, the number of deaths and DALYs from type 2 diabetes due to physical inactivity more than doubled between 1990 and 2019. Concurrently, there was an increase in the ASMR and ASDR, with EAPC of 0.26 (95% CI: 0.13-0.39) and 0.84 (95% CI: 0.78-0.89), respectively. As of 2019, the global ASMR and ASDR for physical inactivity stood at 1.6 (95% UI: 0.8-2.7) per 100 000 and 55.9 (95% UI: 27.2-97.6) per 100 000, respectively. Notable disparities were observed in the type 2 diabetes burden associated with physical inactivity worldwide, with higher sociodemographic index (SDI) countries experiencing lower ASDR and ASMR compared to lower SDI countries. Initially, females exhibited higher ASMR and ASDR than males, but this gender disparity in ASMR and ASDR has lessened in recent years. The mortality and DALYs rates associated with physical inactivity exhibit an inverted V-shaped pattern across various age groups, predominantly affecting the elderly population.Conclusions: Between 1990 and 2019, there was a marked rise in the worldwide burden of type 2 diabetes associated with physical inactivity, underscoring the role of physical inactivity as a key changeable risk factor in the global landscape of this disease.This necessitates additional research to explore the variables contributing to the varying levels of disease burden across different countries and between sexes. Furthermore, it calls for the formulation of public health policies aimed at guiding prevention tactics, promoting early detection, and enhancing the management of type 2 diabetes.